2019
DOI: 10.3390/electronics8060624
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Freeform Lens Device Design with Stearic Acid for A Low-Glare Mosquito-Trapping System with Ultraviolet Light-Emitting Diodes

Abstract: Dengue fever is a public health issue of global concern. Taiwan is located in the subtropical region featuring humid and warm weather, which is conducive to the breeding of mosquitoes and flies. Together with global warming and the increasing frequency of international exchanges, in addition to the outbreak of pandemics and dengue fever, the number of people infected has increased rapidly. This study is dedicated to the development of a new mosquito-trapping system. Research has shown that specific wavelengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Tseng et al reported "Secondary Freeform Lens Device Design with Stearic Acid for A Low-Glare Mosquito-Trapping System with Ultraviolet Light-Emitting Diodes" [9]. This study is dedicated to the development of a new mosquito-trapping system.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%
“…Tseng et al reported "Secondary Freeform Lens Device Design with Stearic Acid for A Low-Glare Mosquito-Trapping System with Ultraviolet Light-Emitting Diodes" [9]. This study is dedicated to the development of a new mosquito-trapping system.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%